Behavioural responses of fish groups exposed to a predatory threat under elevated CO2. (May 2019) - Cattano, C.; Fine, M.; Quattrocchi, F.; Holzman, R.; Milazzo, M.
Abstract: Most of the studies dealing with the effects of ocean acidification (OA) on fish behaviour tested individuals in isolation, even when the examined species live in shoals in the wild. Here we evaluated the effects of elevated CO2 concentrations (i.e. ∼900 μatm) on the shelter use and group cohesion of the gregarious damselfish Chromis viridis using groups of sub-adults exposed to a predatory threat. Results showed that, under predatory threat, fish reared at elevated CO2 concentrations displayed a risky behaviour (i.e. decreased shelter use), whereas their group cohesion was unaffected. Our findings add on increasing evidence to account for social dynamics in OA experiments, as living in groups may compensate for CO2 -induced risky behaviour. Highlights: Only a few studies assessed how ocean acidification affects the behaviour of fish in groups. Shelter use and group cohesion were assessed with or without a predatory threat at high CO2 levels. Fish group behaviour was not affected by elevated CO2 levels in the absence of the predator. Fish groups from elevated CO2 were bolder than control ones under a predatory treat. When a predator was present, group cohesion increased regardless of CO2 conditions.